Mechanisms and treatments of methamphetamine and HIV-1 co-induced neurotoxicity: a systematic review - Miao, Lin; Wang, Haowei; Li, Yi; Huang, Jian; Wang, Chan; Teng, Hanxin; Xu, Lisha; Yang, Xue; Tian, Yunqing; Yang, Genmeng; Li, Juan; Zeng, Xiaofeng (Frontiers in Immunology, 2024)
Combination antiretroviral therapy (cART) has dramatically reduced mortality in people with human immunodeficiency virus (HIV), but it does not completely eradicate the virus from the brain. Patients with long-term HIV-1 infection often show neurocognitive impairment, which severely affects the quality of life of those infected. Methamphetamine (METH) users are at a significantly higher risk of contracting HIV-1 through behaviors such as engaging in high-risk sex or sharing needles, which can lead to transmission of the virus. In addition, HIV-1-infected individuals who abuse METH exhibit higher viral loads and more severe cognitive dysfunction, suggesting that METH exacerbates the neurotoxicity associated with HIV-1. Therefore, this review focuses on various mechanisms underlying METH and HIV-1 co-infection-induced neurotoxicity and existing interventions targeting the sigma 1 receptor, dopamine transporter protein, and other relevant targets are explored. The findings of this review are envisaged to systematically establish a theoretical framework for METH abuse and HIV-1 coinfection-induced neurotoxicity, and to suggest novel clinical treatment targets.